Efficient l-lactic acid production from sweet sorghum bagasse by open simultaneous saccharification and fermentation. Issue 42 (12th April 2016) - Wang, Y.; Wang, M.; Cai, D.; Wang, B.; Wang, Z.; Qin, P.; Tan, T.
Abstract : An open SSF process using B. coagulans LA1507 introduces an effective way to producel -lactic acid from abundant SSB. Abstract : As an important industrial feedstock with various applications, most lactic acid is currently fermented from refined food carbohydrates. To research the feasibility of using non-food feedstock forl -lactic acid production, sweet sorghum bagasse (SSB) as an important lignocellulosic biomass was used by Bacillus coagulans LA1507 in open simultaneous saccharification and fermentation (SSF). In the fed-batch SSF process with a stepwise controlled pH, a cellulase dose of 25 FPU g −1 pretreated SSB and 15 g L −1 corn steep liquor powder (CSLP) were used to producel -lactic acid from 17.5% (w/v) stover, and B. coagulans LA1507 provided a balanced result which contained a product titer of 111 g L −1, a yield of 0.437 g g −1 crude SSB and an average productivity of 1.59 g L −1 h −1 . The process introduces an effective way to producel -lactic acid from abundant SSB.